Persistent Mullerian Duct Syndrome Presenting As Transverse Testicular Ectopia [TTE] Rarest of Rare: A Case Report - SreeRamulu.P.N; D.Srinivasan; Pawan Katti; Madhu (Journal of Krishna Institute of Medical Sciences University, 2015)
Persistent Mullerian Duct Syndrome (PMDS) is usually an accidental finding either during orchipexy or during routine inguinal hernia repair in male patients presenting with mal- descended testes. It is caused by a defect in the Mullerian Inhibiting Substance (MIS) system. Intra-operatively, Mullerian remnants consisting of an infantile uterus and fallopian tubes are usually found. Familiarity with PMDS is necessary to diagnose the condition. We are presenting a rarest of a rare a case report of a male aged 58 year presented with inguino-scrotal swelling. Subsequently the patient was taken up for surgery, when the inguinal canal was opened we found in the hernia sac well developed female reproductive system. i.e. uterus of adult size, ovaries, fallopian tubes and cervix .on the right side hence a case of transverse testicular ectopia, cut sections of uterus shows endometrial cavity measuring 2.5cm, endocervix measuring 2cm while endometrium measuring 1cm. The gonads were testes by histological examination, with features of degeneration and fibrosis with no neoplastic changes